Open Source Archaeology. Ethics and Practice - Wilson, Andrew T. (De Gruyter, 2015)
This edited volume is designed to discuss important issues around open access to data and software in academic and commercial archaeology, as well as to summarise both the current state of theoretical engagement, and technological development in the field of open-archaeology.